A visible light responsive molybdate-based photocatalytic material and its preparation method and application

The Ni3TE1-XTIXMO2-2XW2xo11 type molybdenonate base light catalytic material is adjusted by adjusting tungsten ions and titanium ions to solve the problem of low efficiency of the existing photocatalyst in terms of visible light response, and achieve efficient visible optical response and low efficiency in visible light response. Environmental protection.

CN116422348BActive Publication Date: 2025-01-28CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310651799.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-01-28
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

The existing photocatalysts are inefficient in visible light response, and the bandwidth of traditional semiconductor materials is wide, limiting the utilization of visible light.

Method used

The Ni3Te1-Xtixmo2-2XW2XO11 type of molybdenum acid salt base light catalytic material, through the doping of tungsten ions and titanium ions, adjusts the structure of the material to expand the absorption of visible light.

Benefits of technology

Improving the response ability of photocatalytic materials to visible light, enhanced the optical activity, improved the utilization rate of sunlight, and reduced production costs, and has environmental protection advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116422348B_ABST
    Figure CN116422348B_ABST
Patent Text Reader

Abstract

The present invention provides a visible light responsive molybdate-based photocatalytic material and its preparation method and application, belonging to the technical field of inorganic photocatalytic materials. The chemical formula of the molybdate-based photocatalytic material of the present invention is Ni3Te 1‑x Ti x Mo 2‑2x W 2x O 11 , where x is a tungsten ion (W 6+ ) replaces the molybdenum ion (Mo 6+ ), titanium ions (Ti 4+ ) replaces the tellurium ion (Te 4+ ) and the substitution range is 0.01≤x≤0.1. The doping of impurity ions in the lattice of the photocatalytic material causes the optical cutoff light absorption edge to redshift, expanding the absorption of visible light by the material. At the same time, the lattice disturbance caused by the doping of impurity ions causes certain defects, which can not only reduce the energy band width, but also enhance the electrostatic field and polarization effect in the lattice, which is beneficial to the separation and transmission of photogenerated charges, increase the life of carriers, and enhance the efficiency of photocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic photocatalytic materials, and specifically relates to a molybdate-based photocatalytic material responsive to visible light and a preparation method and application thereof. Background Art

[0002] In order to solve the increasingly serious energy shortage and environmental pollution problems that affect the sustainable development of the economy, photocatalysis has become one of the potential technologies that people are paying attention to. Photocatalysis is the generation of photogenerated electrons and photogenerated holes under the irradiation of light of a certain energy. The photogenerated charges are freed to the surface or interface to undergo redox reactions. The light energy is converted into the energy required for the chemical reaction to produce catalytic effects, so that the surrounding oxygen and water molecules are excited into free anions with strong oxidizing power. These free anions can decompose almost all harmful organic substances and some inorganic substances. This process does not cause waste of resources and does not cause additional pollution. Current research on photocatalysts shows that the main problems affecting their application efficiency are: First, in the photocatalytic process, the photogenerated electrons and holes in traditional photocatalysts are very easy to recombine, resulting in low photocatalytic activity. Second, the wide energy band of semiconductors limits the use of visible light for photocatalysis. For example, anatase TiO 2 The bandgap width of the semiconductor is 3.2 electron volts (387.5 nanometers), which makes its spectral response range mostly in the range of ultraviolet-near ultraviolet wavelengths. Ultraviolet light only accounts for 5% of the solar spectrum. Therefore, the wider energy band makes its photocatalytic activity limited to the ultraviolet range. Generally, the main means to reduce the energy band width of semiconductors and improve the separation efficiency of photogenerated charges are: impurity doping, surface treatment, heterojunction, etc. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art, and provides a molybdate-based photocatalytic material responsive to visible light, and a preparation method and application thereof.

[0004] In one aspect of the present invention, a molybdate-based photocatalytic material responsive to visible light is provided, wherein the chemical formula of the molybdate-based photocatalytic material is Ni 3 Te 1-x Ti x Mo 2-2x W 2x O 11 , where x is a tungsten ion (W 6+ ) replaces the molybdenum ion (Mo 6+ ), titanium ions (Ti 4+ ) replaces the tellurium ion (Te 4+ ), and the range of substitution is 0.01≤x≤0.1.

[0005] Another aspect of the present invention provides a method for preparing the above-mentioned molybdate-based photocatalytic material responsive to visible light, the method comprising:

[0006] According to the chemical formula Ni 3 Te 1-x Ti x Mo 2-2x W 2x O 11 The molar ratio of elements in (0.01≤x≤0.1) is as follows: weigh the compound containing nickel, the compound containing tellurium, the compound containing titanium, the compound containing molybdenum, and the compound containing tungsten respectively;

[0007] The compound containing titanium element is dissolved in anhydrous ethanol, and then glacial acetic acid is added to adjust the pH to 2-6, and stirred for 3-6 hours to obtain a solution containing titanium element;

[0008] The compound containing nickel, the compound containing tellurium, the compound containing molybdenum, and the compound containing tungsten are dissolved in dilute nitric acid and stirred for 2 to 6 hours to form a salt solution;

[0009] Under continuous stirring, slowly drop the salt solution into the solution containing the titanium element, and add an appropriate amount of polyvinyl alcohol and mix and stir for 3 to 6 hours to obtain a mixed solution;

[0010] Aging the mixed solution at room temperature until a transparent gel is formed, and then drying the transparent gel at 75-95° C. to obtain a solidified precursor mixture;

[0011] The precursor mixture is calcined at a temperature of 900 to 1200° C. for 2 to 10 hours to obtain a calcined product; the calcined product is naturally cooled and then ground evenly to obtain a molybdate-based photocatalytic material responsive to visible light.

[0012] Optionally, the compound containing nickel element is one of nickel hydroxide, nickel sulfate, nickel nitrate and nickel chloride.

[0013] Optionally, the compound containing tellurium element is one of tellurium oxide and telluric acid.

[0014] Optionally, the compound containing titanium element is one of tetrabutyl titanate and isopropyl titanate.

[0015] Optionally, the compound containing molybdenum element is one of molybdenum oxide and ammonium molybdate.

[0016] Optionally, the compound containing tungsten element is one of tungsten oxide and ammonium tungstate.

[0017] Optionally, the calcination temperature is 1000-1100° C., and the calcination time is 3-6 hours.

[0018] Another aspect of the present invention provides an application of a visible light responsive molybdate-based photocatalytic material, such as the visible light responsive molybdate-based photocatalytic material described above, which decomposes organic pollutants under visible light irradiation.

[0019] The present invention provides a visible light responsive molybdate-based photocatalytic material and a preparation method and application thereof, which have the following beneficial effects compared with the prior art:

[0020] First, in the photocatalytic material of the present invention, the doping of impurity ions greatly broadens the absorption range of the luminescent material in the visible light wavelength range, thereby improving the utilization rate of sunlight;

[0021] Second, the doping of impurity ions in the photocatalytic material of the present invention causes a certain disturbance in the crystal lattice, thereby enhancing the photocatalytic activity;

[0022] Third, the photocatalytic material of the present invention has the advantages of being environmentally friendly and free of pollution during its preparation process, no waste gas or waste liquid is discharged, the calcination temperature is relatively low, and the production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a flowchart of a method for preparing a molybdate-based photocatalytic material responsive to visible light according to an embodiment of the present invention;

[0024] Figure 2 XRD diffraction patterns of samples prepared in Examples 1, 2, 3, and 4 of the present invention and X-ray diffraction standard card PDF#33-0958 (Ni 3 TeMo 2 O 11 ) comparison results;

[0025] Figure 3 The specific surface area test results of the samples prepared in Examples 1, 2, 3 and 4 of the present invention are as follows;

[0026] Figure 4 The UV-visible absorption spectra of the samples prepared in Examples 1, 2, 3 and 4 of the present invention;

[0027] Figure 5 Degradation curves of the organic dye methylene blue of the samples prepared in Examples 1, 2, 3 and 4 of the present invention;

[0028] Figure 6 The results are the experimental results of the photocatalytic repetitive degradation of the organic dye methylene blue by the sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.

[0030] In one aspect of the present invention, a visible light responsive molybdate-based photocatalytic material is provided. The chemical formula of the molybdate-based photocatalytic material is Ni 3 Te 1-x Ti x Mo 2-2x W 2x O 11 ,

[0031] Where x is a tungsten ion (W 6+ ) replaces the molybdenum ion (Mo 6+ ), titanium ions (Ti 4+ ) replaces the tellurium ion (Te 4+ ), and the range of substitution is 0.01≤x≤0.1.

[0032] In this embodiment, the doping of impurity ions in the lattice of the photocatalytic material causes the optical cutoff light absorption edge to redshift, thereby expanding the absorption of visible light by the material. At the same time, the doping of impurity ions in the lattice causes a strong disturbance of the lattice, which also causes certain defects. Therefore, it can not only reduce the energy band width, but also enhance the electrostatic field and polarization effect in the lattice, which is beneficial to the separation and transmission of photogenerated charges, increase the life of carriers, enhance the photocatalytic activity, and improve the efficiency of photocatalysis.

[0033] The photocatalytic material of this embodiment has good chemical stability, is economical and practical, and is a potential green and environmentally friendly photocatalytic material that responds to visible light.

[0034] like Figure 1 As shown, another aspect of the present invention provides a method S100 for preparing the above-mentioned molybdate-based photocatalytic material responsive to visible light, comprising the following steps S110 to S160:

[0035] S110, according to the chemical formula Ni 3 Te 1-x Ti x Mo 2-2x W 2x O 11The molar ratio of elements in (0.01≤x≤0.1) is such that compounds containing nickel (Ni), tellurium (Te), titanium (Ti), molybdenum (Mo), and tungsten (W) are weighed respectively.

[0036] Specifically, in step S110, the compound containing nickel element is one of nickel hydroxide, nickel sulfate, nickel nitrate and nickel chloride. For example, nickel nitrate may be preferred.

[0037] Further, in step S110, the compound containing tellurium element is one of tellurium oxide and telluric acid. For example, telluric acid may be preferred.

[0038] Furthermore, in step S110, the compound containing titanium element is one of tetrabutyl titanate and isopropyl titanate. For example, tetrabutyl titanate may be preferred.

[0039] Furthermore, in step S110, the compound containing molybdenum element is one of molybdenum oxide and ammonium molybdate. For example, ammonium molybdate may be preferred.

[0040] Furthermore, in step S110, the compound containing tungsten element is one of tungsten oxide and ammonium tungstate. For example, ammonium tungstate may be preferred.

[0041] S120, dissolving the compound containing the titanium element weighed in step S110 in an appropriate amount of anhydrous ethanol, then adding glacial acetic acid to adjust the pH value to 2-6, stirring for 3-6 hours, and obtaining a solution containing the titanium element.

[0042] S130, dissolving the nickel (Ni)-containing compound, tellurium (Te)-containing compound, molybdenum (Mo)-containing compound, and tungsten (W)-containing compound weighed in step S110 in an appropriate amount of dilute nitric acid, stirring thoroughly for 2 to 6 hours, and preparing corresponding salt solutions.

[0043] S140, under continuous stirring, slowly dropwise add the salt solution obtained in step S130 to the solution containing titanium element obtained in step S120, and add a proper amount of polyvinyl alcohol (PVA) and mix and stir for 3 to 6 hours to obtain a mixed solution.

[0044] S150, aging the mixed solution obtained in step S140 at room temperature until a transparent gel is formed, and then placing it in an oven and drying it at 75-95°C to obtain a solidified precursor mixture.

[0045] S160, calcining the precursor mixture obtained in step S150, the calcination temperature is 900-1200° C., and the calcination time is 2-10 hours to obtain a calcined product; then the calcined product is naturally cooled and ground evenly to obtain a molybdate-based photocatalytic material responsive to visible light.

[0046] In step S160, the calcination temperature may preferably be 1000-1100°C, and the calcination time may preferably be 3-6 hours.

[0047] In this embodiment, a molybdate-based photocatalytic material is synthesized by a wet chemical method combined with a sintering method. The preparation process is simple, low-cost, and has good repeatability. The photocatalytic material obtained by this method has good chemical stability, is economical and practical, and is a potential green and environmentally friendly photocatalytic material that responds to visible light.

[0048] Another aspect of the present invention provides an application of a visible light responsive molybdate-based photocatalytic material. The visible light responsive molybdate-based photocatalytic material described above can effectively decompose organic pollutants under visible light irradiation.

[0049] The preparation method and performance of the molybdate-based photocatalytic material responsive to visible light will be further described below in conjunction with several specific examples:

[0050] It should be noted that the photocatalytic test of the following embodiments is evaluated by the degradation activity of methylene blue under the irradiation of visible light. The photocatalytic instrument used is the XPA-2 photolysis instrument produced by Nanjing Xujiang Electromechanical Plant. The light source lamp is a 500-watt cylindrical xenon lamp, and the temperature of the photocatalytic reaction is room temperature. The amount of photocatalytic material used in each experiment is 100 mg, the total solution volume is 250 ml, and the concentration of organic methylene blue is 10 mg / L. The catalyst is added to the reaction solution, and the reaction time is 120 minutes; after opening the condensed water, the illumination is randomly started, and a sample is taken at a customized time after illumination. The upper clear liquid is absorbed by centrifugation, and the light absorption of the methylene blue solution is measured at a wavelength of 650-670 nanometers using a UV-visible spectrophotometer. According to the Lambert-Beer law, the absorbance of the solution is proportional to the concentration, so the absorbance can be used instead of the concentration to calculate the removal rate, which is the removal rate of the methylene blue solution. Calculation formula: Degradation rate = (1-C / C 0 )×100%=(1-A / A 0 )×100%, where C 0 , C are the concentrations before and after photocatalytic degradation, A 0 and A are the absorbance values ​​before and after degradation, respectively.

[0051] Example 1

[0052] The method for preparing the visible light responsive molybdate-based photocatalytic material of this example comprises the following steps:

[0053] S1, according to the chemical formula Ni 3 Te 0.9 Ti 0.1 Mo 1.8 W 0.2 O 11 The molar ratio of the elements in the reaction mixture was 6.979 g of nickel nitrate, 1.534 g of telluric acid, 0.272 g of tetrabutyl titanate, 2.541 g of ammonium molybdate, and 4.057 g of ammonium tungstate;

[0054] S2, dissolving the tetrabutyl titanate weighed in step S1 in an appropriate amount of anhydrous ethanol, then adding an appropriate amount of glacial acetic acid, adjusting the pH to 2, and stirring thoroughly for 3 hours;

[0055] S3, dissolving the nickel nitrate, telluric acid, ammonium molybdate and ammonium tungstate weighed in step S1 in an appropriate amount of dilute nitric acid, stirring for 6 hours to prepare a transparent salt solution;

[0056] S4. Under continuous stirring, slowly drop the salt solution prepared in step S3 into the solution obtained by dissolving tetrabutyl titanate in step S2, and add an appropriate amount of PVA, mix and stir for 6 hours;

[0057] S5, aging the mixed solution obtained in step S4 at room temperature for a certain period of time until a transparent gel is formed, and then placing it in an oven and drying it at 95° C. for a certain period of time to obtain a precursor mixture;

[0058] S6. The precursor mixture obtained in step S5 is placed in a muffle furnace for calcination at a temperature of 1200° C. for 4 hours. The calcined product is naturally cooled and then ground appropriately to obtain a molybdate-based photocatalytic material responsive to visible light.

[0059] Further, see Appendix Figure 2 , the comparison results of the X-ray powder diffraction patterns of the samples prepared in each embodiment and the X-ray diffraction standard card PDF#33-0958 are given. Referring to the X-ray powder diffraction pattern of the sample prepared according to the technical scheme of Example 1, it can be seen that the experimental data is completely consistent with the standard card, indicating that the prepared material has a single-phase composition and good crystallinity.

[0060] For further information, see Appendix Figure 3 , the specific surface area test results of the samples prepared in each embodiment are given. Referring to the adsorption-desorption curve of the sample prepared according to the technical scheme of Example 1, it can be seen that its specific surface area is 27.5 square meters / gram.

[0061] For further information, see Appendix Figure 4, the UV-visible absorption spectrum test results of the samples prepared in each embodiment are given. Referring to the UV-visible absorption spectrum of the sample prepared according to the technical scheme of Example 1, it can be seen that its light absorption cutoff absorption edge is approximately located at 550 nanometers.

[0062] For further information, see Appendix Figure 5 , the degradation curves of methylene blue for samples prepared by the technical solutions of each embodiment are given. Referring to the degradation curve of the sample prepared by the technical solution of Example 1, it can be seen that the degradation rate of methylene blue by photocatalytic degradation of the sample can reach more than 98% in 120 minutes, indicating that the material has efficient photocatalytic activity.

[0063] For further information, see Appendix Figure 6 , is the repeated effect of the sample prepared according to the technical solution of Example 1 on the photocatalytic degradation of methyl blue. It can be seen from the figure that after three rounds of repeated experiments, the photocatalytic degradation of methylene blue by the sample is still very good.

[0064] Example 2

[0065] The method for preparing the visible light responsive molybdate-based photocatalytic material of this example comprises the following steps:

[0066] S1, according to the chemical formula Ni 3 Te 0.92 Ti 0.08 Mo 1.84 W 0.16 O 11 The molar ratio of the elements in the reaction mixture was 6.194 g nickel nitrate, 1.467 g telluric acid, 0.241 g tetrabutyl titanate, 2.306 g ammonium molybdate, and 2.879 g ammonium tungstate;

[0067] S2, dissolving the tetrabutyl titanate weighed in step S1 in an appropriate amount of anhydrous ethanol, then adding an appropriate amount of glacial acetic acid, adjusting the pH to 6, and stirring thoroughly for 6 hours;

[0068] S3, dissolving the nickel nitrate, telluric acid, ammonium molybdate and ammonium tungstate weighed in step S1 in an appropriate amount of dilute nitric acid, stirring thoroughly for 2 hours to prepare a transparent salt solution;

[0069] S4, under continuous stirring, slowly dropwise add the salt solution prepared in step S3 to the solution obtained by dissolving tetrabutyl titanate in step S2, and add an appropriate amount of PVA, mix and stir for 3 hours;

[0070] S5, aging the mixed solution obtained in step S4 at room temperature for a certain period of time until a transparent gel is formed, and then placing it in an oven and drying it at 75° C. for a certain period of time to obtain a precursor mixture;

[0071] S6. The precursor mixture obtained in step S5 is placed in a muffle furnace for calcination at a temperature of 900° C. for 10 hours. The calcined product is naturally cooled and then ground appropriately to obtain a molybdate-based photocatalytic material responsive to visible light.

[0072] Further, see Appendix Figure 2 , the comparison results of the X-ray powder diffraction patterns of the samples prepared in each embodiment and the X-ray diffraction standard card PDF#33-0958 are given. Referring to the X-ray powder diffraction pattern of the sample prepared according to the technical scheme of Example 2, it can be seen that the experimental data is completely consistent with the standard card, indicating that the prepared material has a single-phase composition and good crystallinity.

[0073] For further information, see Appendix Figure 3 , the specific surface area test results of the samples prepared in each embodiment are given. Referring to the adsorption-desorption curve of the sample prepared according to the technical scheme of Example 2, it can be seen that its specific surface area is 24.7 square meters / gram.

[0074] For further information, see Appendix Figure 4 , the UV-visible absorption spectra of the samples prepared in each embodiment are given. Referring to the UV-visible absorption spectrum of the sample prepared according to the technical scheme of Example 2, it can be seen that its light absorption cutoff absorption edge is approximately located at 520 nanometers.

[0075] For further information, see Appendix Figure 5 , the degradation curves of methylene blue for samples prepared by the technical solutions of each embodiment are given. Referring to the degradation curve of the sample prepared by the technical solution of Example 2, it can be seen that the degradation rate of methylene blue by photocatalytic degradation of the sample can reach more than 91% in 120 minutes, and the material has high efficient photocatalytic activity.

[0076] Example 3

[0077] The method for preparing the visible light responsive molybdate-based photocatalytic material of this example comprises the following steps:

[0078] S1, according to the chemical formula Ni 3 Te 0.95 Ti 0.05 Mo 1.9 W 0.1 O 11 The molar ratio of the elements in the reaction mixture was as follows: 8.723 g nickel nitrate, 2.067 g telluric acid, 0.341 g tetrabutyl titanate, 3.349 g ammonium molybdate, and 0.258 g ammonium tungstate;

[0079] S2, dissolving the tetrabutyl titanate weighed in step S1 in an appropriate amount of anhydrous ethanol, then adding an appropriate amount of glacial acetic acid, adjusting the pH to 3, and stirring thoroughly for 5 hours;

[0080] S3, dissolving the nickel nitrate, telluric acid, ammonium molybdate and ammonium tungstate weighed in step S1 in an appropriate amount of dilute nitric acid, stirring thoroughly for 3 hours to prepare a transparent salt solution;

[0081] S4, under continuous stirring, slowly dropwise add the salt solution prepared in step S3 to the solution obtained by dissolving tetrabutyl titanate in step S2, and add an appropriate amount of PVA, mix and stir for 3 hours;

[0082] S5, aging the mixed solution obtained in step S4 at room temperature for a certain period of time until a transparent gel is formed, and then placing it in an oven and drying it at 75° C. for a certain period of time to obtain a precursor mixture;

[0083] S6. The precursor mixture obtained in step S5 is placed in a muffle furnace for calcination at a temperature of 1000° C. for 5 hours. The calcined product is naturally cooled and then ground appropriately to obtain a molybdate-based photocatalytic material responsive to visible light.

[0084] Further, see Appendix Figure 2 , a comparison between the X-ray powder diffraction patterns of the samples prepared in each embodiment and the X-ray diffraction standard card PDF#33-0958 is given. Referring to the X-ray powder diffraction pattern of the sample prepared according to the technical scheme of Example 3, it can be seen that the experimental data is completely consistent with the comparison of the standard card, and the prepared material has a single-phase composition and good crystallinity.

[0085] For further information, see Appendix Figure 3 , the specific surface area test results of the samples prepared in each embodiment are given. Referring to the adsorption-desorption curve of the sample prepared according to the technical scheme of Example 3, it can be seen that its specific surface area is 22.2 square meters / gram.

[0086] For further information, see Appendix Figure 4 , the UV-visible absorption spectrum test results of the samples prepared in each embodiment are given. Referring to the UV-visible absorption spectrum of the sample prepared according to the technical scheme of Example 3, it can be seen that its light absorption cutoff absorption edge is approximately located at 475 nanometers.

[0087] For further information, see Appendix Figure 5 , the degradation curves of methylene blue of the samples prepared by the technical solutions of each embodiment are given. Referring to the degradation curve of the sample prepared by the technical solution of Example 3, it can be seen that the degradation rate of methylene blue by photocatalytic degradation of the sample can reach more than 75% in 120 minutes, and the material has efficient photocatalytic activity.

[0088] Example 4

[0089] The method for preparing the visible light responsive molybdate-based photocatalytic material of this example comprises the following steps:

[0090] S1, according to the chemical formula Ni 3 Te 0.99 Ti 0.01 Mo 1.98 W 0.02 O 11 The molar ratio of the elements in the reaction mixture was as follows: 16.575 g nickel nitrate, 3.926 g telluric acid, 0.646 g tetrabutyl titanate, 6.643 g ammonium molybdate, and 0.101 g ammonium tungstate;

[0091] S2, dissolving the tetrabutyl titanate weighed in step S1 in an appropriate amount of anhydrous ethanol, then adding an appropriate amount of glacial acetic acid, adjusting the pH to 3, and stirring thoroughly for 5 hours;

[0092] S3, dissolving the nickel nitrate, telluric acid, ammonium molybdate and ammonium tungstate weighed in step S1 in an appropriate amount of dilute nitric acid, stirring thoroughly for 3 hours to prepare a transparent salt solution;

[0093] S4, under continuous stirring, slowly dropwise add the salt solution prepared in step S3 to the solution obtained by dissolving tetrabutyl titanate in step S2, and add an appropriate amount of PVA, mix and stir for 3 hours;

[0094] S5, aging the mixed solution obtained in step S4 at room temperature for a certain period of time until a transparent gel is formed, and then placing it in an oven and drying it at 75° C. for a certain period of time to obtain a precursor mixture;

[0095] S6. The precursor mixture obtained in step S5 is placed in a muffle furnace and calcined at a temperature of 1050° C. for 5 hours. The calcined product is naturally cooled and then ground appropriately to obtain a molybdate-based photocatalytic material responsive to visible light.

[0096] Further, see Appendix Figure 2 , the comparison results of the X-ray powder diffraction patterns of the samples prepared in each embodiment and the X-ray diffraction standard card PDF#33-0958 are given. Referring to the X-ray powder diffraction pattern of the sample prepared according to the technical scheme of Example 4, it can be seen that the experimental data is completely consistent with the standard card, indicating that the prepared material has a single-phase composition and good crystallinity.

[0097] For further information, see Appendix Figure 3 , the specific surface area test results of the samples prepared in each embodiment are given. Referring to the adsorption-desorption of the sample prepared according to the technical scheme of Example 4, it can be seen that its specific surface area is 19.81 square meters / gram.

[0098] For further information, see Appendix Figure 4, the UV-visible absorption spectra of the samples prepared in each embodiment are given. Referring to the UV-visible absorption spectrum of the sample prepared according to the technical scheme of Example 4, it can be seen that its light absorption cutoff absorption edge is approximately located at 445 nanometers; from the experiment, it can be seen that the doping of impurity ions greatly improves the absorption of visible light by the material.

[0099] For further information, see Appendix Figure 5 , the degradation curves of methylene blue of the samples prepared by the technical solutions of each embodiment are given. Referring to the degradation curve of the sample prepared by the technical solution of Example 4, it can be seen that the degradation rate of methylene blue by photocatalytic degradation of the sample can reach 50% in 120 minutes.

[0100] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A visible light responsive molybdate-based photocatalytic material, characterized in that: The chemical formula of the molybdate-based photocatalytic material is Ni3Te 1-x Ti x Mo 2-2x W 2x O 11 , where x is the tungsten ion W 6+ Replace molybdenum ion Mo 6+ 、Ti ion Ti 4+ Substitute tellurium ion Te 4+ The molybdate-based photocatalytic material is obtained by the following method: According to the chemical formula Ni3Te 1-x Ti x Mo 2-2x W 2x O 11 According to the molar ratio of the elements in the formula, weigh the compound containing nickel, the compound containing tellurium, the compound containing titanium, the compound containing molybdenum, and the compound containing tungsten respectively; The compound containing titanium element is dissolved in anhydrous ethanol, and then glacial acetic acid is added to adjust the pH to 2-6, and stirred for 3-6 hours to obtain a solution containing titanium element; The compound containing nickel, the compound containing tellurium, the compound containing molybdenum, and the compound containing tungsten are dissolved in dilute nitric acid and stirred for 2 to 6 hours to form a salt solution; Under continuous stirring, slowly drop the salt solution into the solution containing the titanium element, and add an appropriate amount of polyvinyl alcohol and mix and stir for 3 to 6 hours to obtain a mixed solution; Aging the mixed solution at room temperature until a transparent gel is formed, and then drying the transparent gel at 75-95° C. to obtain a solidified precursor mixture; The precursor mixture is calcined at a temperature of 900 to 1200° C. for 2 to 10 hours to obtain a calcined product; the calcined product is naturally cooled and then ground evenly to obtain a molybdate-based photocatalytic material responsive to visible light.

2. A method for preparing the visible light responsive molybdate-based photocatalytic material according to claim 1, characterized in that: The method comprises: According to the chemical formula Ni3Te 1-x Ti x Mo 2-2x W 2x O 11 The molar ratio of the elements in the formula (a) is 0.01≤x≤0.1, and the compound containing nickel, the compound containing tellurium, the compound containing titanium, the compound containing molybdenum, and the compound containing tungsten are weighed respectively; The compound containing titanium element is dissolved in anhydrous ethanol, and then glacial acetic acid is added to adjust the pH to 2-6, and stirred for 3-6 hours to obtain a solution containing titanium element; The compound containing nickel, the compound containing tellurium, the compound containing molybdenum, and the compound containing tungsten are dissolved in dilute nitric acid and stirred for 2 to 6 hours to form a salt solution; Under continuous stirring, slowly drop the salt solution into the solution containing the titanium element, and add an appropriate amount of polyvinyl alcohol and mix and stir for 3 to 6 hours to obtain a mixed solution; Aging the mixed solution at room temperature until a transparent gel is formed, and then drying the transparent gel at 75-95° C. to obtain a solidified precursor mixture; The precursor mixture is calcined at a temperature of 900 to 1200° C. for 2 to 10 hours to obtain a calcined product; the calcined product is naturally cooled and then ground evenly to obtain a molybdate-based photocatalytic material responsive to visible light.

3. The method according to claim 2, characterized in that The compound containing nickel element is one of nickel hydroxide, nickel sulfate, nickel nitrate and nickel chloride.

4. The method according to claim 2, characterized in that: The compound containing tellurium element is one of tellurium oxide and telluric acid.

5. The method according to claim 2, characterized in that: The compound containing titanium element is one of tetrabutyl titanate and isopropyl titanate.

6. The method according to claim 2, characterized in that The compound containing molybdenum element is one of molybdenum oxide and ammonium molybdate.

7. The method according to claim 2, characterized in that The compound containing tungsten element is one of tungsten oxide and ammonium tungstate.

8. The method according to claim 2, characterized in that: The calcination temperature is 1000-1100° C., and the calcination time is 3-6 hours.

9. Application of a visible light responsive molybdate-based photocatalytic material, characterized in that: The visible light responsive molybdate-based photocatalytic material as claimed in claim 1 decomposes organic pollutants under visible light irradiation.

Citation Information

Patent Citations

  • Zeolite-based nano bismuth molybdate visible light catalytic material and preparation method thereof

    CN101444744A

  • Preparing method and application of novel visible-light responding photocatalyst Li3Ni2NbO6

    CN105688923A